The protocol for developing health and disease prevention services: An exercise-based prediction model integrating genomic test results. - Yunsuk Choi; Hyunseok Jee (PLoS ONE, 2025)
Background Cancer is a leading cause of mortality worldwide, with approximately 19.6 million new cases and 10 million deaths reported in 2020. Exercise interventions have demonstrated positive effects on physical and mental health in cancer patients, yet there is limited evidence on the efficacy of tailored, high-intensity exercise programs designed using genomic data. This protocol outlines a study aimed at integrating genomic analysis and personalized exercise interventions to improve health outcomes and reduce cancer-related risk factors. This study aims to evaluate the feasibility and potential impact of a personalized exercise intervention delivered through the EXESALUS mobile application. The program integrates genomic information to tailor exercise regimens for cancer prevention, muscle strength improvement, and quality-of-life enhancement. Methods This is a protocol for a 3-month, parallel-group, randomized controlled trial involving 500 participants, including 100 cancer patients undergoing treatment or rehabilitation and 300 non-cancer participants with elevated disease risk. Participants will engage in the EXESALUS program, which includes low-, moderate-, and high-intensity exercise tailored to genomic profiles, supported by exercise counseling and wearable device feedback. Biospecimens (blood, urine, and oral epithelial cells) will be collected at baseline, 6 weeks, and 3 months to assess genomic variations and physiological changes. Primary outcomes include physical performance (SPPB), muscle strength (1RM and peak power), and skeletal muscle mass (DXA). Secondary outcomes will evaluate mental health indicators such as fatigue (FACIT-F), resilience, anxiety, depression, and quality of life. Discussion This study will provide a detailed framework for implementing ICT-based personalized exercise interventions that incorporate genomic analysis. The EXESALUS program is expected to highlight the potential of tailored high-intensity exercise as a preventive and therapeutic strategy for cancer patients and individuals at risk of chronic diseases. The findings of this protocol will contribute to the development of precision medicine approaches for cancer prevention and management, emphasizing the scalability and utility of ICT-based solutions in health promotion. Trial registration This study was registered in the Korean Clinical Trials Registry (KCT0010187).